2005
DOI: 10.1021/jp053907y
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Benzene Dication [C6H6]2+:  Exploring the Potential Energy Surface

Abstract: The singlet potential energy surface for the dissociation of benzene dication has been explored, and its three major dissociation channels have been studied: C6H6(2+) --> C3H3(+) + C3H3(+), C4H3(+) + C2H3(+), and C5H3(+) + CH3(+). The calculated energetics suggest that the products will be formed with considerable translational energy because of the Coulomb repulsion between the charged fragments. The calculated energy release in the three channels shows a qualitative agreement with the experimentally observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…In all calculations, the low lying triplet and singlet states appear to be very close in energy. 31,33,34 The present theoretical results confirm that the most stable state is a singlet one. It has also to be noted, when looking at the spin of product ions, that the dissociative channels here studied are consistent with a precursor dication in a singlet state.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In all calculations, the low lying triplet and singlet states appear to be very close in energy. 31,33,34 The present theoretical results confirm that the most stable state is a singlet one. It has also to be noted, when looking at the spin of product ions, that the dissociative channels here studied are consistent with a precursor dication in a singlet state.…”
Section: Discussionsupporting
confidence: 82%
“…The analysis of such a spectrum, when combined with some calculated energy levels, 33 appears to be consistent with the formation of the dication in a triplet ground state. However, other more recent theoretical works 31,34 found that the ground state is a singlet. In all calculations, the low lying triplet and singlet states appear to be very close in energy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The mechanisms proposed so far all describe a single, specific fragmentation pathway involving ring opening followed by migration of the two nearest protons to the end of the chain and abstraction of the CH 3 + ion. 29,30 Based on our observations this mechanism cannot fully explain the dissociation reaction. For the proposed pathway no CH 3 + and CD 3 + should be observed for the partially deuterated benzene.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies of the protonated polyacetylenes include data from calculations, [1][2][3][4] mass spectrometry, 1,5,6 and matrix-isolation experiments of their electronic absorption spectra; 7 to this day the gas phase spectra have not been reported. To measure these an apparatus has been built which incorporates the cooling capabilities of a 22-pole ion trap.…”
Section: Introductionmentioning
confidence: 99%